Accessibilities and population potentials of “central place”: An approach from Thuringia - Gather, Matthias (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
In the course of up-dating the State Development Plan for the federal state of Thuringia, and against the backdrop of dwindling populations and improvements in accessibility, the decision was taken to overhaul the “central-place” concept introduced in 1993. Drawing on accessibility analyses based on private-car use, the future population potentials of so-called “higher-order centres” have been recalculated in order to gauge the long-term significance of such centres for spatial planning within the state. In the light of current levels of infrastructure endowment and capacity utilisation, the authors are able to proceed to formulating recommendations for a future system of “central places” which strives to mediate between blanket supply and economic viability. The current and anticipated shortcomings thus revealed in respect of accessibility provide important pointers toward the types of supplementary structure-policy measures which the state will need to adopt in the future.